Effectiveness of Prenatal Yoga on Quality Improvement Pregnant Women's Sleep in the Third Trimester - Farokah, Atik; Kurniasari, Eri (MultiTech Publisher, 2024)
Pregnant women in the third trimester experience physical and psychological changes. This condition causes pregnant women to experience discomfort such as sleep disturbances. One way to overcome this condition is by doing prenatal yoga. This study aims to determine the effectiveness of prenatal yoga in improving the sleep quality of pregnant women in the third trimester. This research uses a Quasi Experimental method with a One Group Pretest-Posttest Design. The sample in this study consisted of 30 pregnant women in the third trimester using a purposive sampling technique. This research was carried out in March-May 2023. Data was collected by observation and analyzed using non-parametric tests. Univariate analysis results showed that the average sleep quality was before (mean = 9.20 and SD = 1.476) and after (mean = 5 and SD = 0.816). Bivariate analysis results showed that there was an effect of prenatal yoga on improving sleep quality in third trimester pregnant women with a Z value = 2.871 and p value = 0.004. So, it can be concluded that there is an influence of prenatal yoga on improving sleep quality in third trimester pregnant women.